The Relationship Between Organizational Activities and Students' Interpersonal Ability: Hubungan Antara Keaktifan Berorganisasi dengan Kemampuan Interpersonal Mahasiswa - Arianti, Ninik; Ansyah, Eko Hardi (Psikologia : Jurnal Psikologi, 2023)
The purpose of this study was to determine the relationship between organizational activity and interpersonal skills of adolescents in Trompo Asri Jabon Sidoarjo. This study uses a quantitative approach. In this study, a sample of 46 students in Trompo Asri Village, Jabon Sidoarjo, was used which was obtained from the total sampling technique. The data collection technique was carried out with the scale of organizational activity and the scale of interpersonal skills. Measurement of variables using a Likert scale. The data were analyzed by testing the hypothesis using the Pearson Correlaton Product Moment. The results of this study indicate that there is a significant relationship between organizational activity and interpersonal skills in students in Trompo Asri Village. Students' organizational activities in Trompo Asri Village are classified as active, while students' interpersonal skills in Trompo Asri Village are classified as good.